A retrospective review of the factors that negatively influenced the eradication of polio in South-South, Nigeria - Grace E, Peters; Victor, Assi; Nnabuike E, Oko; Etete J, Peters (Journal of Community Medicine and Health Solutions, 2021)
Background: The endemic nature of poliomyelitis in Nigeria was a source of concern to many given the global efforts aimed at eradicating the scourge. In this study, the factors that influenced the eradication of this malady in South-South Nigeria (Akwa Ibom and Cross River State) were investigated. Four null hypotheses, drawn on these factors (including culture belief, religious difference, language and the prevalence of ethnic conflict) guided the investigation. The main thrust of this study was to examine how socio-cultural factors negatively influenced the eradication of polio in the study area. Methods: Through stratified random and purposive sampling techniques, 600 adult men and women who had children were selected for the study. A structured questionnaire constructed by the researcher was used in data collection. Data analysis was carried out using one-way ANOVA and independent t-test statistical tools. Results: The findings were that cultural belief and religious affiliation exerted significant influence on the people’s effort towards polio eradication. Conclusion: The study indicated that the low use of health services by the people was brought about by variation in these variables. Among other things, it was suggested that continuous awareness campaigns be carried out to educate the people on the need for immunization anchored in science and technology.